1/y-1/y-3 = (y-3)/y(y-3) - y/y(y-3)
= (y-3)-y/y(y-3)
= -3/y(y-3)
2007-01-12 09:15:22
·
answer #1
·
answered by Elena A 1
·
0⤊
0⤋
-3
2007-01-12 09:13:56
·
answer #2
·
answered by TRACY B 1
·
0⤊
0⤋
I suspect you want some brackets to clarify ...
1/y - 1/y = 0
So 1/y - 1/y - 3 = -3
My guess, though, is that you mean
(1/y) - (1/(y-3))
Cross multiply to give a common denominator
= ((y-3) - y) / (y(y-3))
= -3 / (y^2 - 3y)
2007-01-12 09:10:21
·
answer #3
·
answered by Dr Bob UK 3
·
1⤊
0⤋
a million.Simplify the expression: a million/y - a million/y-3 a million/y - a million/(y - 3) liquid crystal show = y(y - 3) a million(y - 3)/[y(y - 3)] - 1y/[y(y - 3)] (y - 3 - y)/[y(y - 3)] -3/[y(y - 3)] 2) a. (a+b) (a-c) = a^2 - ac + ab - bc b. (3a^2+4b)/(ac+3b) = (3a^2+4b)/(ac+3b) 3) (x^2-10x+25)/(x^2-5x) aspect numerator and denominator [(x - 5)(x - 5)]/[x(x - 5)] (x - 5)/x 4. d(A, C) + d(B, C) [ 10 - (-5) + (10 - 3) = 15 + 7 = 22 5. x^ - 5 distinction of two squares a^2 - b^2 = (a + b)(a - b) 5 = [sqrt(5)]^2 [x + sqrt(5)][x - sqrt(5)]
2016-12-02 04:27:20
·
answer #4
·
answered by santella 4
·
0⤊
0⤋
1/y - 1/y leaves zero so then you're just left with the -3 as the answer.
2007-01-12 09:06:53
·
answer #5
·
answered by mickeymouse 2
·
1⤊
0⤋
Simplify 1/y-1/y-3.
(1/y) - (1/y) = 0
So
1/y-1/y-3 = -3
But I suspect you meant:
1/y - 1/(y - 3)
In that case:
1/y - 1/(y - 3) = {(y - 3) - y}/{y(y - 3)} = -3 / {y(y - 3)}
In the future please use parentheses to eliminate ambiguity.
2007-01-12 10:33:44
·
answer #6
·
answered by Northstar 7
·
0⤊
0⤋
1/y - 1/(y-3)=
Find the common denominator: y*(y-3)
(y-3)/ [y*(y-3)] - (y)/ [y*(y-3)] =
-3/ [y*(y-3)] =
-3/ (y^2-3y)
2007-01-12 09:13:05
·
answer #7
·
answered by Jerry P 6
·
0⤊
0⤋
(y-3)-y/y(y-3)=
y-y-3/y^2-3y
-3/y^2-3y
2007-01-12 09:11:55
·
answer #8
·
answered by Anonymous
·
0⤊
0⤋